The impact of agro-food industry on regional employment and population changes: The case of Denmark and France - Jens Abildtrup; Virginie Piguet; Bertrand Schmitt (European Regional Science Association (ERSA), 2010)
In the European rural development policy special emphasis is placed on support of the agro-food industry which is regarded as an important economic development driver in rural areas. This paper analyses and compares the employment and population changes in Denmark and France in the period 1990 - 2006, applying a regional adjustment model. We modify the classical Boarnet model by addressing the employment in the agro-food, manufacturing, and services sectors explicitly. Besides revealing the interactions between employment in the three analysed sectors and between employment and population changes we estimate the impact of exogenous factors, e.g. amenities and public services, on employment and population changes. To account for spatial error autocorrelation the model is estimated, applying a generalized spatial two-stage least squares procedure. The empirical results for both countries do not support the export base hypothesis, i.e. growth in the manufacturing sector employment is not driving employment in the service sector. However, considering the agro-food sector there are indications of a positive impact of employment growth in this sector on the service sector employment growth. In Denmark, the agro-food employment growth has also a positive impact on the employment growth in export sector and on the population growth, indicating that the focus on the agro-food sector in rural development policies may be reasonable.
Keywords: 330